2012
DOI: 10.1590/s1516-35982012000700026
|View full text |Cite
|
Sign up to set email alerts
|

Rumen fermentation and nutrient flow to the omasum in Holstein cows fed extruded canola seeds treated with or without lignosulfonate

Abstract: -Four multiparous Holstein cows averaging 548 kg of body weight and 74 d in lactation were used in a Latin square design with four 21-d experimental periods to determine effects of feeding extruded versus non-extruded canola seed, with or without 50 g/kg lignosulfonate on rumen fermentation, nutrient flow to the omasum, and degradability of dry matter (DM) and N of each diet. The DM effective degradability increased with extrusion and lignosulfonate treatment had no effect.The effective degradability of N was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It has been reported that doses of tannins higher than 0.5% of diet DM may decrease the rate of nutrient digestion in the rumen (Mueller-Harvey, 2006). In contrast, some studies have reported a non-harmful effect of tannin extract on ruminant intake (Al-Kindi et al, 2016;Santos et al, 2012). In this study, we decided to use a dose of condensed tannins that is approximately ten times lower than the usual doses reported in most studies in the literature to minimize further negative effects, mainly on DMI and ruminal deamination, which are also effects promoted by sodium monensin (Duffield et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that doses of tannins higher than 0.5% of diet DM may decrease the rate of nutrient digestion in the rumen (Mueller-Harvey, 2006). In contrast, some studies have reported a non-harmful effect of tannin extract on ruminant intake (Al-Kindi et al, 2016;Santos et al, 2012). In this study, we decided to use a dose of condensed tannins that is approximately ten times lower than the usual doses reported in most studies in the literature to minimize further negative effects, mainly on DMI and ruminal deamination, which are also effects promoted by sodium monensin (Duffield et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also obtained by Doreau et al [53], who studied the effect of linseed lipid on ruminal metabolism and intestinal digestibility in cows and reported no change in protozoal number when cows' diet was supplemented with either rolled flaxseed or a mixture of flax oil and flax meal. Santos et al [54] stated that the inclusion of canola seeds had no effect on the pH, ammonia nitrogen, and VFA values in the rumen. They reported that extruded canola seeds might stimulate the efficiency of microbial protein synthesis and, thus, increase protein availability in the small intestine without compromising the total digestibility of protein.…”
Section: Ruminal Fermentationmentioning
confidence: 99%
“…Among the five studies submitted, two cannot be considered since one (Petit et al., ) is an in vitro study and the other (Rosa dos Santos et al., ) lacks to report any performance parameters. The remaining three are not tolerance studies since only one lignosulphonate dose level was introduced and the duration was very short (20 and 21 days in two studies).…”
Section: Assessmentmentioning
confidence: 99%
“…Rosa dos Santos et al. () assessed the effects of feeding extruded versus non‐extruded canola seed, with or without 50,000 mg lignosulphonate/kg on rumen fermentation, nutrient flow to the omasum and degradability of DM and N of each diet. Four multiparous Holstein cows were used in a Latin square design with four 21‐day experimental periods.…”
Section: Assessmentmentioning
confidence: 99%